Rosuvastatin, Sildenafil and Their Combination in Monocrotaline-Induced Pulmonary Hypertension in Rat - Jasińska-Stroschein Magdalena; Owczarek Jacek; Wesołowska Anna; Orszulak-Michalak Daria (Acta Pharmaceutica)
There is considerable interest in the pleiotropic effects of statins and their potential role in the treatment of pulmonary hypertension. Previous experimental findings indicate that a combination of lipophilic statins with phosphodiesterase type-5 inhibitor, sildenafil, can offer preventive effects on rat monocrotaline-induced pulmonary hypertension. The present study is aimed to assess whether therapeutic regimen provides any benefits. Seven days after pulmonary hypertension induction, hydrophilic rosuvastatin and sildenafil were given for 14 days to male Wistar outbred rats. Right ventricular pressure, right ventricle mass and three biomarkers were evaluated after 21 days: brain natriuretic peptide, high-density lipoprotein cholesterol and vascular endothelial growth factor. The present study demonstrates that administration of hydrophilic statin with sildenafil results in reduction of pulmonary vascular remodeling and right ventricular pressure. The results of biochemical measurements may suggest that statins play a positive role in right ventricle function or the process of angiogenesis in pulmonary hypertension development.